Molecular control of normal and acrocona mutant seed cone development in Norway spruce (Picea abies) and the evolution of conifer ovule-bearing organs - Carlsbecker, Annelie; Sundstrom, Jens F; Englund, Marie; Uddenberg, Daniel; Izquierdo, Liz; Kvarnheden, Anders; Vergara-Silva, Francisco; Engstrom, Peter (The New phytologist, 2013)
Reproductive organs in seed plants are morphologically divergent and their evolutionary history is often unclear. The mechanisms controlling their development have been extensively studied in angiosperms but are poorly understood in conifers and other gymnosperms. Here, we address the molecular control of seed cone development in Norway spruce, Picea abies. We present expression analyses of five novel MADS-box genes in comparison with previously identified MADS and LEAFY genes at distinct developmental stages. In addition, we have characterized the homeotic transformation from vegetative shoot to female cone and associated changes in regulatory gene expression patterns occurring in the acrocona mutant. The analyses identified genes active at the onset of ovuliferous and ovule development and identified expression patterns marking distinct domains of the ovuliferous scale. The reproductive transformation in acrocona involves the activation of all tested genes normally active in early cone development, except for an AGAMOUS-LIKE6/SEPALLATA (AGL6/SEP) homologue. This absence may be functionally associated with the nondeterminate development of the acrocona ovule-bearing scales. Our morphological and gene expression analyses give support to the hypothesis that the modern cone is a complex structure, and the ovuliferous scale the result of reductions and compactions of an ovule-bearing axillary short shoot in cones of Paleozoic conifers.